PTU-104 Thioguanine nucleotides: optimising thiopurine therapy in inflammatory bowel disease (a DGH perspective). (28th May 2012) - Pee, L; Gera, A; Bedwell, T; Saxena, V; Curtis, H; Loganayagam, A
Abstract : Introduction: Azathioprine (AZA) and 6-mercaptopurine (6MP) have been used in treatment of inflammatory bowel disease since introduction in the 1960s. 1 6-thioguanine nucleotides (TGN) levels are related to therapeutic response with likely minimum threshold value of 235–250 pmol/8×10 8 RBC. 2–5 8 Thiopurine metabolism is affected by thiopurine methyltransferase (TPMT) and its activity is therefore important. Methylated derivatives like 6 methyl mercaptopurine 6 7 (MMP) are possibly partially responsible for hepatotoxic effects and maximum threshold value has been established at 5700 pmol/ 8× 10 8 RBC in a paediatric IBD population. 2 Methods: TGN/MMP measurements for the period October 2010–October 2011 were obtained from the biochemistry lab at Queen Elizabeth Hospital Woolwich and Queen Mary's Hospital Sidcup and notes were reviewed. Data were collected regarding indications, drug therapy, TPMT levels prior to therapy (if available), concurrent blood results and action taken with the results. Results: 110 TGN/MMP measurements were taken on 86 patients (43 Male) with average age 40 years (17–73). 46 had Crohn's disease, 38 had ulcerative colitis and two had indeterminate colitis. TPMT was measured in 53 patients (62%) with average level 31 pm/hr/mgH (15–46). 10 patients were deficient (16–25 pm/hr/mgH). Nine patients had above average activity (>40 pm/hr/mgH). 72 tests carried out with patients on AZA, 29 tests on 6-MP and eight tests on AZA/Allopurinol. Six patients had dose reduction due to high TGN/MMP levels, five dose increase, seven escalated to biologic therapy, two medication changes to thioguanine or methotrexate and three switched to AZA/Allopurinol. One patient on 6-MP had abnormal LFTs despite normal MMP (4663) and TPMT (37) levels which settled once 6-MP was stopped. Another patient had TGN/MMP levels of 0 but denied non-compliance and was subsequently given biologic therapy. In this cohort, 24 (28%) patients had medication adjustments as a result of TGN/MMP measurements and 3 (3.5%) had compliance addressed with serial TGN results showing positive results. Conclusion: Our experience with TGN/MMP measurements indicates that they are a useful tool in optimising thiopurine therapy and can be used to determine dose adjustment or if new therapies are needed in poor responders. Non-compliance can also be determined and tackled. Additionally, they can be used to address hepatotoxicity due to high MMP levels as this can be circumvented by adding allopurinol to thiopurines at 25%–50% of usual dose. 9 Competing interests: None declared. References: 1. Med J Aust 1962;49 :592–3. 2. Gastroenterology 2000;118 :705–13. 3. Gastroenterology 2006;130 :1047–53. 4. Gut 2001;48 :642–6. 5. Gut 2004;53 :1123–8. 6. Rev Gastroenterol Disord 2003;3 (S1):S30–8. 7. Gut 1996;39 :401–6. 8. Aliment Pharmacol Ther 2005;21 :829–39. 9. Aliment Pharmacol Ther 2012;35 :15–36.